Dampak Gaya Visual Anime terhadap Respons Konsumen dalam Iklan YouTube di Indonesia - Muhammad Vibra Bagaskoro; Rivaldi Fatwa Dwi Putra; Albertus Agung Dewa (International Forum of Researchers and Lecturers, 2025)
Anime has become a significant global phenomenon, including in Indonesia, where this culture has influenced various aspects of society. This article explores the impact of anime visual style in YouTube advertisements in Indonesia. The influence of anime on Indonesian society is also evident in the consumption trends of products related to Japanese culture. The involvement of Indonesian society with anime has also encouraged the emergence of various businesses and products that capitalize on the popularity of this culture. This study focuses on exploring the impact of anime visual style on consumer responses in the context of advertising through YouTube social media in Indonesia. The researcher will analyze how the use of anime elements in advertisements can influence consumer perceptions, whether through nostalgia, enjoyment, or aesthetic aspects, as well as how marketing strategies can be adjusted to maximize this effect. The research method uses content analysis of social media comments as research data. Three advertising samples were selected to represent the study. The results of the analysis show that the use of anime elements in advertisements for Pop Mie, McDonald's, and Pocari Sweat successfully attracted attention and created positive responses from consumers. The high quality of the animation and the use of anime visual styles created a strong emotional appeal, even influencing consumer behavior such as product preferences and interest in brands. In conclusion, the use of anime visual styles in Pop Mie, McDonald's, and Pocari Sweat advertisements demonstrates the success of a marketing strategy that utilizes the popularity of anime to attract attention and create emotional engagement. and influencing consumer behavior in Indonesia, as well as opening opportunities for more local anime production and strengthening positive brand image. This advertisement is not only an effective marketing tool, but also opens up opportunities for more local anime production and supports a positive brand image.